Innovation Capability and Sustainable Performance Through Knowledge Management in Small and Medium-sized Enterprises - Pham, Anh Tuan; Pham, Quoc Trung (Journal of Knowledge Management Practice, 2024)
Knowledge management (KM) across organizations is based on the realization that integrating knowledge or more broadly intellectual capital (IC) both inside and outside the enterprise helps enhance the innovation capability (INC) and sustainable performance (SUP) of enterprises. The purpose of this study is to examine the effects of internal intellectual capital (IIC), external intellectual capital (EIC), and social capital (SOC) on INC and SUP through KM in SMEs. The survey questionnaire was sent to managers working in Vietnamese SMEs. SPSS and AMOS software were used for data analysis. The results indicate that IIC, EIC, and SOC have positive impacts on the INC and SUP of SMEs through KM activities. These findings hope to be useful for scholars and especially SME owners to understand more thoroughly the relationships between IC, SOC, and KM, as well as the influence of these relationships on INC and SUP, while providing new insight and useful suggestions for owners of SMEs in acquiring and exploiting knowledge from outside to fill knowledge gaps within the enterprise.
Keywords: knowledge management; innovation capability; sustainable performance